The Role of Parents in the Children’s Spiritual Development at UNKLAB Adventist High School - Septian Dwi Kusuma; Juwinner Dedy Kasingku (Edumaspul: Jurnal Pendidikan, 2024)
Parents naturally hope for their children to become good individuals, and even the best. Therefore, parents play a crucial role in educating and shaping their children's spirituality. In education, character growth can impact spirituality. Thus, it is important to teach children about spirituality and character simultaneously. The aim of this research is to determine whether there is a relationship between parental roles in the development of children's spirituality in UNKLAB Adventist High School. This research utilizes a quantitative method with a descriptive correlational design through a cross-sectional approach. Sampling is conducted using convenience sampling technique with a total of 105 respondents. Out of the total 105 respondents from class XI, it was found that parents actively participate in developing their children's spirituality. The Parental role variable showed an average value of 4.02, and the children's spirituality variable showed an average value of 4.03. Furthermore, a significant relationship was observed between parental roles in the development of children's spirituality at UNKLAB Adventist High School with a p-value of 0.000 <0.05 and an r-value of 0.548, indicating a strong correlation. It is recommended for parents to maintain or even enhance their roles within the family, especially in educating their children in spirituality